(untitled) (Bangladesh Journal of Urology, 2022)
Objective: In standard PCNL usually placement of a double J stent and a nephrostomy tube is required.Several recent studies have reported the benefits of tubeless percutaneous nephrolithotomy (PCNL). Postoperatively,In standard PCNL patients have an indwelling ureteric stent placed, which is often associated with stent-related morbidity. We performed totally tubeless(without any stent or nephrostomy tube) PCNL.This study was conducted in the urology centre of Combined military Hospital,Dhaka, to evaluate the safety, effectiveness, and feasibility of totally tubeless PCNL and to compare with standard PCNL where both nephrostomy tube and double J stent were placed. Materials and Methods: From January 2018 to June 2019 , total 57 selected patients underwent standard or totally tubeless PCNL.In standard PCNL group, both D-J stent and nephrostomy tube were placed and Neither a nephrostomy tube nor a ureteral stent was placed in the totally tubeless PCNL group. We compared patient demographics and stone characteristics, operation time, length of hospital stay, analgesia requirements, stonefree rate, blood loss, change in creatinine, and postoperative complications between the standard and totally tubeless PCNL groups. Results: There were no significant differences in preoperative patient characteristics, postoperative complications, and the stone-free rate between the two groups, but the totally tubeless PCNL group showed a shorter hospital stay and a lesser analgesic requirement compared with the standard PCNL group. Blood loss and change in serum creatinine level were not significantly different between the two groups. Conclusions: Totally tubeless PCNL appears to be a safe and effective alternative for the management of renal stone in selected patients and is associated with a shorter length of hospital stay and less analgesic requirement. Bangladesh J. Urol. 2021; 24(1): 53-57